On-Board and Intercept Transit Survey Techniques - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s Transit Cooperative Research Program (TCRP) Synthesis 63: On-Board and Intercept Transit Survey Techniques examines transit agencies2019 experiences with planning and implementing on-board and intercept surveys. On-board and intercept surveys include self-administered surveys distributed on board buses and railcars, and in stations, as well as interviews conducted in these environments. The report provides an overview of industry practices and covers a broad range of issues addressed in planning a given survey.

Review of Progress in Astronomy and Astrophysics Toward the Decadal Vision: Letter Report - National Research Council (The National Academies Press, 2005)
In the past few years, programmatic changes at NASA, issues raised by the NRC report, Connecting Quarks with the Cosmos: Eleven Science Questions for the New Century(CQC), and scientific and technological advances combined to prompt consideration of a reexamination of the overall science strategy set forth in Astronomy and Astrophysics in the New Millennium (AANM). Discussions followed between the Board on Physics and Astronomy and NASA and NSF that resulted in a request by the two agencies to prepare a short report addressing the points leading up to calls for the reexamination. The report was also to assess progress towards the vision set forth in the AANM and CQC studies. This letter report presents the result of that study. It reviews the context that led up to the request and the most exciting advances in astronomy and astrophysics and key technological developments since the AAMN report was published, and it provides an outlook for fulfilling the decadal vision of the two previous studies.

Public Transportation Emergency Mobilization and Emergency Operations Guide: Appendix B–Survey of U. S. Public Transportation Systems - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB's Transit Cooperative Research Program (TCRP) Web Only Document 25, Public Transportation Emergency Mobilization Guide: Appendix B2014Survey of U. S. Public Transportation Systems includes additional information on the survey used as input on TCRP Report 86: Public Transportation Security, Volume 7 with the same title. TCRP Report 86 examines actions that may be taken by public transportation agencies working with their local communities to promote the early recognition of emergency events, expedite response to emergency events, establish multi-agency coordination, and ensure that public transportation resources are available to support the response to an emergency event.The TCRP Report 86: Public Transportation Security series assembles relevant information into single, concise volumes, each pertaining to a specific security problem and closely related issues. These volumes focus on the concerns that transit agencies are addressing when developing programs in response to the terrorist attacks of September 11, 2001, and the anthrax attacks that followed. Future volumes of the report will be issued as they are completed.

Earth Science and Applications from Space: Urgent Needs and Opportunities to Serve the Nation - National Research Council (The National Academies Press, 2005)
The Earth is a dynamic planet whose changes and variations affect our communications, energy, health, food, housing, and transportation infrastructure. Understanding these changes requires a range of observations acquired from a variety of land-, sea-, air-, and space-based platforms. To assist NASA, NOAA, and the USGS develop these tools, the NRC was asked by these agencies to carry out a decadal strategy survey of Earth science and applications from space. In particular, the study is to develop the key scientific questions on which to focus Earth and environmental observations in the period 2005-2015, and a prioritized list of space programs, missions, and supporting activities to address these questions. This interim report outlines a key element of the study2014the rationale for tying Earth observations to societal need2014and identifies urgent near-term actions needed to achieve this goal. A final report, due in late 2006, will provide the list of recommended space missions, programs, and supporting.

Science in NASA's Vision for Space Exploration - National Research Council (The National Academies Press, 2005)
In January 2004, President Bush announced a new space policy directed at human and robotic exploration of space. The National Academies released a report at the same time that independently addressed many of the issues contained in the new policy. In June, the President2019s Commission on Implementation of United States Space Exploration Policy issued a report recommending that NASA ask the National Research Council (NRC) to reevaluate space science priorities to take advantage of the exploration vision. Congress also directed the NRC to conduct a thorough review of the science NASA is proposing to undertake within the initiative. This report provides an initial response to those requests. It presents guiding principles for selecting science missions that enhance and support the exploration program. The report also presents findings and recommendations to help guide NASA2019s space exploration strategic planning activity. Separate NRC reviews will be carried out of strategic roadmaps that NASA is developing to implement the policy.

The Atacama Large Millimeter Array: Implications of a Potential Descope - National Research Council (The National Academies Press, 2005)
The 1991 NRC decadal survey for astronomy and astrophysics included a project called the Millimeter Array (MMA). This instrument would be an array of millimeter-wavelength telescopes intended to capture images of star-forming regions and distant star-burst galaxies. With the addition of contributions form Europe, the MMA evolved into the Atacama Large Millimeter Array (ALMA), a proposed array of 64, 12-meter antennas. The project is now part of the NSF Major Research Equipment and Facilities budget request. Increased costs, however, have forced the NSF to reconsider the number of antennas. To help with that review, NSF asked the NRC to assess the scientific consequences of reducing the number of active antennas from 60 to either 50 or 40. This report presents an assessment of the effect of downsizing on technical performance specifications, performance degradation, and the ability to perform transformational science, and of the minimum number of antennas needed.

Strategic Planning and Management in Transit Agencies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s Transit Cooperative Research Program (TCRP) Synthesis 59: Strategic Planning and Management in Transit Agencies examines the value and benefits of strategic planning and management in transit agencies. The report also provides case studies from five transit agencies based on the comprehensiveness of process or presence of innovative or noteworthy practices.

Measuring Research and Development Expenditures in the U.S. Economy - National Research Council (The National Academies Press, 2005)
This report examines the portfolio of research and development (R&D) expenditure surveys at the National Science Foundation (NSF), identifying gaps and weaknesses and areas of missing coverage. The report takes an in-depth look at the definition of R&D, the needs and potential uses of NSF2019s R&D data by a variety of users, the goals of an integrated system of surveys and other data collection activities, and the quality of the data collected in the existing Science Resources Statistics surveys.

Improving the Safety of Older Road Users - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 348: Improving the Safety of Older Road Users examines programs and policies in place across the country to improve the safety and mobility of older road users. The report documents a range of strategies and related programs under way in roadway engineering, driver licensing, public information and education, and enforcement and adjudication.

Measuring Food Insecurity and Hunger: Phase 1 Report - National Research Council (The National Academies Press, 2005)

Appendixes to TCRP Report 107: Analyzing the Effectiveness of Commuter Benefits Programs - Transportation Research Board; Transportation Research Board (The National Academies Press, 2005)
TRB's Transit Cooperative Research Program (TCRP) Web Only Document 27: Appendixes to TCRP Report 107: Analyzing the Effectiveness of Commuter Benefits Programs includes information on TCRP Report 107's methodology, summary tables, survey descriptions, case studies, and more.

Motorcoach Industry Hours of Service and Fatigue Management Techniques - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 7: Motorcoach Industry Hours of Service and Fatigue Management Techniques identifies and documents the unique features of the extended workday that typifies motorcoach operations and identifies techniques that motorcoach managers, front-line employees, and drivers use to reduce fatigue-related incidents resulting from the irregular on-duty conditions facing the motorcoach driver. The synthesis also identifies current and emerging technologies that may be appropriate for motorcoach operations to offset the effects of the extended workday and fatigue-inducing environment.

Practices in No-Show and Late Cancellation Policies for ADA Paratransit - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s Transit Cooperative Research Program (TCRP) Synthesis 60: Practices in No-Show and Late Cancellation Policies for ADA Paratransit examines current and innovative practices of U.S. transit agencies in the development and implementation of passenger no-show and late cancellation policies for paratransit programs operated under the regulatory requirements of the Americans with Disabilities Act of 1990 (ADA). The report reviews the administration, community response, and effectiveness of policies in small, medium, and large transit agencies. The report addresses policies as a way to improve system productivity, efficiency, and capacity, and as a means to better service riders with disabilities who may experience difficulties with the advance reservation aspect of most ADA complementary paratransit operations.

Crash Records Systems - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 350: Crash Records Systems examines crash records systems practices and programs as applied to highway and traffic safety. The report covers crash data collection, crash processing and management, and data linkages for reporting and analysis. While no single comprehensive system examples are identified in the report, many examples of one or more successful components were found to address the needs of three groups of stakeholders2014data collectors, data managers, and data users. The report also contains information about lessons learned from examples of successful systems, addressing the needs and concerns of stakeholders.

Inspection and Management of Bridges with Fracture-Critical Details - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 354: Inspection and Management of Bridges with Fracture-Critical Details explores the inspection and maintenance of bridges with fracture-critical members (FCMs), as defined in the American Association of State Highway and Transportation Officials2019 Load and Resistance Factor Design (LRFD) Bridge Design Specifications. The report identifies gaps in literature related to the subject; determines practices and problems with how bridge owners define, identify, document, inspect, and manage bridges with fracture-critical details; and identifies specific research needs. Among the areas examined in the report are inspection frequencies and procedures; methods for calculating remaining fatigue life; qualification, availability, and training of inspectors; cost of inspection programs; instances where inspection programs prevented failures; retrofit techniques; fabrication methods and inspections; and experience with fracture-critical members fractures and problems details.

Steel Bridge Erection Practices - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 345: Steel Bridge Erection Practices examines steel bridge erection practices for I-girder, tub-girder, and box-girder bridges; particularly curved, skewed, and staged structures. The report focuses on the impact of design and analysis practices on erection; methods used to predict erection deflections as a function of bridge type and complexity; shop-assembly practices and alternate methods of ensuring properly assembled geometry; stability issues; field connection practices; examples of structures in which erection practices have caused problems; owner requirements for erection procedures, implementation of requirements, and the impact of procedures on the quality of erection; and current and proposed research.

Improving Data to Analyze Food and Nutrition Policies - National Research Council (The National Academies Press, 2005)
Several changes in the United States over the past two decades have implications for diet, nutrition, and food safety, including patterns of food consumption that have produced an increase in overweight and obese Americans and threats to food safety from pathogens and bioterrorism. The changes raise a number of critical policy and research questions: How do differences in food prices and availability or in households' time resources for shopping and food preparation affect what people consume and where they eat? How do factors outside of the household, such as the availability of stores and restaurants, food preparation technology, and food marketing and labeling policies, affect what people are consuming? What effects have food assistance programs had on the nutritional quality of diets and the health of those served by the programs? Where do people buy and consume food and how does food preparation affect food safety? To address these and related questions, the Economic Research Service (ERS) of the U.S. Department of Agriculture (USDA) asked the Committee on National Statistics to convene a panel of experts to provide advice for improving the data infrastructure on food consumption and nutrition. The panel was charged to review data needs to support research and decision making for food and nutrition policies and programs in USDA and to assess the adequacy of the current data infrastructure and recommend enhancements to improve it. The primary basis for the panel's deliberations, given limited resources, was a workshop on Enhancing the Data Infrastructure in Support of Food and Nutrition Programs, Research, and Decision Making, which the panel convened on May 27-28, 2004. This report is based on the discussions at the workshop and the deliberations of the panel. The report outlines key data that are needed to better address questions related to food consumption, diet, and health; discusses the available data and some limitations of those data; and offers recommendations for improvements in those data. The panel was charged to consider USDA data needs for policy making and the focus of the report is on those needs.

Integrated Roadside Vegetation Management - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2005)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 341: Integrated Roadside Vegetation Management examines the incorporation of integrated roadside vegetation management decision-making processes into highway project planning, design, construction, and maintenance. The report also documents existing roadside vegetation management research and practice.

The Geological Record of Ecological Dynamics: Understanding the Biotic Effects of Future Environmental Change - National Research Council (The National Academies Press, 2005)
In order to answer important questions about ecosystems and biodiversity, scientists can look to the past geological record2014which includes fossils, sediment and ice cores, and tree rings. Because of recent advances in earth scientists2019 ability to analyze biological and environmental information from geological data, the National Science Foundation and the U.S. Geological Survey asked a National Research Council (NRC) committee to assess the scientific opportunities provided by the geologic record and recommend how scientists can take advantage of these opportunities for the nation2019s benefit. The committee identified three initiatives for future research to be developed over the next decade: (1) use the geological record as a 201cnatural laboratory201d to explore changes in living things under a range of past conditions, (2) use the record to better predict the response of biological systems to climate change, and (3) use geologic information to evaluate the effects of human and non-human factors on ecosystems. The committee also offered suggestions for improving the field through better training, improved databases, and additional funding.

Expanding Access to Research Data: Reconciling Risks and Opportunities - National Research Council (The National Academies Press, 2005)
Policy makers need information about the nation2014ranging from trends in the overall economy down to the use by individuals of Medicare2014in order to evaluate existing programs and to develop new ones. This information often comes from research based on data about individual people, households, and businesses and other organizations, collected by statistical agencies. The benefit of increasing data accessibility to researchers and analysts is better informed public policy. To realize this benefit, a variety of modes for data access2014 including restricted access to confidential data and unrestricted access to appropriately altered public-use data2014must be used. The risk of expanded access to potentially sensitive data is the increased probability of breaching the confidentiality of the data and, in turn, eroding public confidence in the data collection enterprise. Indeed, the statistical system of the United States ultimately depends on the willingness of the public to provide the information on which research data are based. Expanding Access to Research Data issues guidance on how to more fully exploit these tradeoffs. The panel2019s recommendations focus on needs highlighted by legal, social, and technological changes that have occurred during the last decade.